2021
DOI: 10.1029/2020jd033137
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft‐Based Observations of Ozone‐Depleting Substances in the Upper Troposphere and Lower Stratosphere in and Above the Asian Summer Monsoon

Abstract: The Asian summer monsoon anticyclone (ASMA) occurs during the boreal summer (July, August, and September) over East and South Asia. It is a major meteorological system characterized by deep convection and anticyclonic flow in the upper troposphere and lower stratosphere (UTLS) and is subject to strong

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…VSLS have been found to make an important contribution to stratospheric halogen loading and thus polar ozone destruction (World Meteorological Organization [WMO], 2018). Airborne in situ measurements in the ASM convective transport region during the StratoClim campaign found much higher than the previously estimated background concentrations (by ∼ a factor of 2) of Chlorinated VSLS at the tropopause level (Adcock et al., 2021), providing observational evidence that the ASM is an important source region for halogenated VSLS (Engel et al., 2018). The contribution of ASM transport to stratospheric ozone chemistry is an important motivation for characterizing this transport pathway in ACCLIP.…”
Section: Vertical Structure and The Depth Of The Asm Transport Into S...mentioning
confidence: 79%
See 1 more Smart Citation
“…VSLS have been found to make an important contribution to stratospheric halogen loading and thus polar ozone destruction (World Meteorological Organization [WMO], 2018). Airborne in situ measurements in the ASM convective transport region during the StratoClim campaign found much higher than the previously estimated background concentrations (by ∼ a factor of 2) of Chlorinated VSLS at the tropopause level (Adcock et al., 2021), providing observational evidence that the ASM is an important source region for halogenated VSLS (Engel et al., 2018). The contribution of ASM transport to stratospheric ozone chemistry is an important motivation for characterizing this transport pathway in ACCLIP.…”
Section: Vertical Structure and The Depth Of The Asm Transport Into S...mentioning
confidence: 79%
“…Also planned are balloon‐borne measurements of aerosol and water vapor profiles to complement the airborne studies. This project follows and complements the Stratospheric and upper tropospheric processes for better Climate predictions (StratoClim; http://www.stratoclim.org/) project, which conducted high‐altitude research flights from Kathmandu, Nepal, and successfully sampled chemical distributions of a suite of trace gases and aerosols near the center of the ASM anticyclone during July–August 2017 (Adcock et al., 2021; Bucci et al., 2020; Höpfner et al., 2019; Mahnke et al., 2021; von Hobe et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The post-flight spectral analysis of the collected data for the detection of O 3 , NO 2 , and BrO is based on the DOAS method (differential optical absorption spectroscopy; Platt and Stutz, 2008). For the UV spectrometer retrieval of BrO differential slant column densities (dSCD), given in molecules per square centimeter, a fit window of 346−359 nm is used as suggested by Aliwell et al (2002), i.e., a two-band fit of the vibrational transitions 4.0 and 5.0 of the A 2 3/2 ← X 2 3/2 electronic transition (Wilmouth et al, 1999). For O 3 -UV dSCDs, used as the corresponding scaling gas, a fit window of 338−357 nm is applied (Puk , īte and Wagner, 2016).…”
Section: Mini-doas Measurements Of O 3 No 2 and Bromentioning
confidence: 99%
“…Spectral retrieval absorption cross sections used for the DOAS method analysis (Hüneke et al, 2017;Stutz et al, 2017). The solar I 0 correction used is suggested in Aliwell et al (2002).…”
Section: Mini-doas Measurements Of O 3 No 2 and Bromentioning
confidence: 99%
“…The 1992 Montreal Protocol concluded with the agreement to ban the production of CFCs in the world. However, banning the production of CFCs does not mean in any way that CFCs have disappeared from the atmosphere [3]. With data from the Earth System Research Laboratory/NOAA, it is observed that in the case of CFC-12, the current concentration is of the same order of magnitude as in 1990 (500 ppt); in the case of CFC-11, the current concentration is of the same order of magnitude as in 1985 (230 ppt); while the concentration of HCFC-22 went from 50 ppt in 1980 to 260 ppt in 2018 [4] [5].…”
Section: Introductionmentioning
confidence: 99%